Improving the Performance of Wood Adhesive with Waste Rubber Tire - Matchawet, Suradet; Johns, Jobish; Artchomphoo, Jutatip; Boonsong, Kwanruethai; Sookyung, Uraiwan (Trends in Sciences, 2023)
Reclaimed rubber (RR) from waste tires was introduced as a wood adhesive by blending with epoxidized natural rubber (ENR). To improve the polarity of RR and compatibility with ENR, maleic anhydride (MA) was grafted onto RR chains. Influences of RR and RR-g-MA (maleic anhydride grafted reclaimed rubber) on the adhesion of wood adhesive along with their properties such as crosslinking, mechanical properties, thermal stability, and wettability were studied. It was found that RR and RR-g-MA affect the vulcanization of ENR by increasing crosslink density. Especially, in the case of using RR-g-MA generates a new form of an ester linkage. The higher crosslink density together with the formation of ester linkages results in superior thermal stability by the addition of RR-g-MA. In addition, the incorporation of RR exhibited an increase in the lap shear strength when compared with the pure ENR. This improvement is due to the increased crosslink density because the presence of RR resulted in the enhanced cohesive strength of rubber adhesive. Additionally, the incorporation of RR-g-MA showed higher efficiency to improve the adhesion of rubber adhesive. The addition of RR-g-MA has not only enhanced the cohesive strength of rubber adhesive, but also increased the adhesive strength from the interaction between the hydroxy group in cellulose on the wood surface and the polar functional group (i.e., oxirane rings of ENR, maleic group of RR-g-MA and ester group of ester linkage) of rubber adhesive. Therefore, the cohesive fracture was observed in ENR/RR-g-MA adhesive. HIGHLIGHTS The worn-out rubber tire as a mass waste can be utilized to develop effective adhesives The addition of maleic anhydride grafted reclaimed rubber caused to generate new ester linkage between epoxidized natural rubber chains The epoxidized natural rubber vulcanizates with maleic anhydride grafted reclaimed rubber showed superior thermal stability The addition of maleic anhydride grafted reclaimed rubber enhanced the adhesive strength of rubber adhesive from the interaction between hydroxy group in cellulose on the wood surface and the polar functional group of rubber adhesive GRAPHICAL ABSTRACT